До питання надійності активних моніторингових геодезичних мереж - Третяк, К. Р.; Савчин, І. Р. (Видавництво Львівської політехніки, 2013)
Используя метод математического моделирования, выведена функция зависимости надежности активных мониторинговых геодезических сетей от определителя ковариационной матрицы ( критерия D) и процента использованных избыточных измерений. Using the method of mathematical modeling, we have derived the function of dependence of the reliability of active geodetic network for deformation monitoring on covariance matrix determinant (D criterion) and the measurement schemes in a network.